Leiomyosarcoma of the Renal Vein Mimicking a Primitive Renal Cell Carcinoma: Case Report of an Unusual Presentation - Amal Fekkar; Hafsa Elouazzani; Ahmed Jahid; Kaoutar Znati; Fouad Zouaidia; Zakia Bernoussi (Case Reports in Pathology)
Primary leiomyosarcomas (LMS) of vascular origin are rare tumors, and more than half of the cases arise in the inferior vena cava (IVC). Primary LMS of the renal vein are extremely rare tumors with only a few cases reported in the literature. Their diagnosis is made only by pathological features. Histologically, they are made of atypical spindle-shaped cells arranged in long intersecting fascicles. Tumor cells stain positive for myogenic markers in immunohistochemistry. Standard treatment consists of radical nephrectomy followed by chemotherapy and/or radiotherapy. Because of insufficient histological data and follow-up, the prognosis factors are not well identified. Overall prognosis of renal vein LMS is poor. We report here an exceptional case of a huge LMS of the right renal vein mimicking a primitive renal cell carcinoma, occurring in a 56-year-old male patient.